Effect of Collaborative Culture on Innovation in Nepalese Hotels: Mediation By Knowledge Sharing and Moderation By Self-Efficacy and Experience - Raut, Sabina (Nepalese Journal of Hospitality and Tourism Management, 2025)
This research investigates the association between collaborative culture (Cc) and creative capabilities in five-star hotels in Kathmandu, Nepal, connecting Social Cognitive Theory. This study examines the impact of collaborative culture on knowledge sharing and assesses whether knowledge sharing (ks) mediates the relationship between collaborative culture and innovative capability. The study also examines the moderating effects of education and work experience on this association. A cross-sectional quantitative approach was utilized to gather data from 215 hotel employees, comprising managers, supervisors, and junior staff, using convenience sampling. The results indicate that a collaborative culture enhances knowledge sharing. Knowledge sharing and self-efficacy are positively associated with innovative capability. A collaborative culture negatively impacts innovative capabilities. Knowledge sharing facilitates the connection between collaborative culture and creative capabilities. Self-efficacy and work experience substantially influenced the relationships examined. These findings highlight the significance of cultivating collaborative culture to improve innovation capacity in the hospitality industry. In this study, ks is not considered as a construct or part rather its influence collaborative culture.Cc is the part of organizational culture represent environmental aspect whereas ks represents behavioral aspect.